VARIABLE RHYTHMS IN GROUNDWATER REGIME AND THEIR RELATIONSHIP WITH CLIMATE FACTORS - Shevchenko, O.; Skorbun, A.; Osadchiy, V.; Charny, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Due to the anomalous changes in the groundwater regime over the past 5 years, the question arose about the adequacy and effectiveness of existing methods for predicting their level. The data of monitoring observations from 1951 in the upper part of the Southern Bug river basin are analyzed. The specific underground runoff to the river in the site of Khmilnyk was calculated by the finite difference method. It is established that at the end of the 80s of the last century a 7-8 year cycle began to appear in the fluctuations of the groundwater level (GWT) and groundwater runoff. It correlates well with the cyclicity of the air temperature, and, to a lesser extent, with the cycles of the monthly amount of precipitation. Instead, such rhythms are not at all typical of solar activity, which is characterized by 11-year and 5-6-year cycles. It is in connection with them that the heliosynoptic method of long-term prediction of RGV is based. It is likely that temperature changes occurring on Earth may change the "sun-induced" cyclicity of GWT, so this method of forecasting becomes ineffective. As there is no clear link between temperature changes and solar activity, it is possible that temperature changes are caused by human activity.From 2013-2015, with the beginning of the low water cycle in the study area, the anomalous minima in the GWT mode became more frequent and the cycles were transformed in the direction of their reduction (up to 5-6 years), which may indicate sharp changes in the nature of groundwater storage recovery. Deviations from 8-year cycles and differences in their duration in different parts of the same catchment area are primarily related to differences of GWT. Wavelet analysis was used as the main method of cyclic selection. Using multiple correlation analysis, it was found that in recent decades the temperature has reached a dominant position in terms of the impact on the groundwater regime (at their levels from 1.5 to 4.0 m). As a result, it was noted that our 7-8 year cycles are well traced during the relatively multi-water period caused by increased infiltration of groundwater due to increasing winter thaws (one of the most significant manifestations of global warming), and 5-6 year cycles correspond to low water periods.
Keywords: cyclicity; groundwater levels; underground runoff to the river; wavelet analysis; regime; temperature; solar activity; precipitation; observations; river Southern Bug